PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBASIS MASALAH TERHADAP HASIL BELAJAR IPS PESERTA DIDIK KELAS VIII SMP NEGERI 1 TRIMURJO - Lutfi Annisa; Wakijo Wakijo (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2019)
Make A Match is a group learning model that invites students to understand a concept or topic through paired card games that can make students more active in following the learning process in the classroom so that students can improve their learning outcomes. The problem in the research conducted by researchers is "There are still many students who have not experienced mastery learning in the social studies learning outcomes of eighth grade students of SMP Negeri 1 Trimurjo 2018/2019 academic year". From these problems, the formulation of the problem in the study is "The Effect of Using Cooperative Learning Model Type Make A Match Based Problems Against Social Studies Learning Outcomes of Grade VIII Students of SMP Negeri 1 Trimurjo in the Academic Year of 2018/2019". Based on the problem formulation the research objective is to know The Effect of Using Cooperative Learning Models Type Make A Match Based Problems on Social Studies Learning Outcomes of VIII Grade Students of SMP Negeri 1 Trimurjo in the Academic Year of 2018/2019. This study uses an experimental method (Quasi Experimental), with an experimental design form, the form of The Non-Equivalent Control Group Design: In this design the experimental and control groups were not chosen randomly but with purposive sampling techniques.Based on the results of the research conducted, the hypothesis was accepted, because the value of tcount> ttable can be seen in the attachment list G, at a significant level of 5%, namely 6 , 80> 1.70. Students who were declared complete with KKM were (72) after being given treatment with the problem-based Make A Match cooperative learning model, 24 students or 80% percentage, while the students in the unfinished category were 6 students or with a percentage of 20%. Thus it shows that there is a positive influence on the use of problem-based Make A Match cooperative learning models for social studies learning outcomes of class VIII students of SMP Negeri 1 Trimurjo in the Academic Year of 2018/2019.Keywords: Cooperative Learning Model Type Make A Match Based on Problems, Social Studies Learning Outcomes.